Reinventing matchmakers: Ethnography of a matrimonial service agency in urban China La réinvention des marieuses Ethnographie d'une agence matrimoniale en Chine urbaine - Pettier, Jean-Baptiste (Homme, 2019)
Matchmakers are an ancient social institution in China. In order to control families and social mores, the imperial state had long imposed their use. Considered as an obstacle to the emancipation of the new generations at the turn of the twentieth century, and as such as a cause of China's lagging behind, they were forbidden by the Communist regime. However, the practice of matchmaking never completely disappeared at all, and the economic reforms implemented since the 1980s seem to have accelerated its reinvention. Whereas traditionally matchmakers were an indispensable part of any « respectable» wedding, today, however, they connote a lack of personal autonomy on the part of the wedding couple. Thus, the changed social position of the matchmakers transforms classical theoretical questions concerning the role of the individual and his/her personal sentiments in the choice of a spouse in China. his articles demonstrates how through the present ethnography of a marriage service agency in the city of Chengdu.
CRIS-Team Scopus Importer:2023-03-21
Keywords: China; Family; Individuals; Marriage; Matchmaker; Modernity; Sentiments